Pengaruh Earning Per Share, Price Earning Ratio, Return On Equity, dan Debt to Equity Ratio terhadap Return Saham : (Studi Empiris pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di BEI) - Rudyansyah Fadil Al Zuhra; Tri Widyastuti; Pratiwi Nila Sari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to examine whether there is an effect of earning per share, price earning ratio, return on equity, and debt to equity ratio on stock returns, especially in food and beverage sector manufacturing companies. The method used in this research is quantitative research method and the data used is secondary data. The population and samples used in this study are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique was carried out using purposive sampling technique which resulted in a sample of 21 companies with 4 years of observation, so 84 data samples were obtained. The data analysis method used is descriptive statistical analysis test, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. besides using multiple regression analysis analysis test and hypothesis testing consisting of determination coefficient test and t test. The results of data analysis show that partially earning per share has a positive effect on stock returns, price earning ratio has a positive effect on stock returns, return on equity has a positive effect on stock returns, and debt to equity ratio have no influence on stock returns.